Meningkatkan prestasi belajar IPS melalui pembelajaran kooperatif model TPS pada siswa kelas IV SD - Misata Misata (Jurnal Riset Teknologi dan Inovasi Pendidikan (Jartika), 2018)
The purpose of this study was to determine the effect of cooperative learning Think-Pair-Share models on the results of learning social science towards Class IV Elementary Students. This research is an action research as many as three cycles. Each cycle consists of four stages, namely: design, activity and observation, reflection, and revision. Data obtained in the form of formative test results, observation sheets of teaching and learning activities. From the results of data analysis, it was found that students' learning achievement had increased from cycle I to cycle III, namely, cycle I (60.71%), cycle II (75.00%), and cycle III (89.29%). So the conclusion of this study is that the cooperative method of Think-Pair-Share model can have a positive effect on student learning motivation, and this learning model can be used as an alternative to social science